The Effect of Gender Equality on Poverty Rate in Surabaya City and Gresik Regency - Rahma Febriana; Sishadiyati Sishadiyati (Cita konsultindo, 2024)
Surabaya City and Gresik Regency have mostly female productive-age population. With the opportunity of a large number of female productive age population and as an industrial area, Surabaya City and Gresik Regency should be able to take advantage of this in reducing the poverty rate. Therefore, the purpose of this study is to determine the effect of gender equality as seen through the contribution of women's income, GDI, and the female labor force participation rate on the poverty rate in Surabaya City and Gresik Regency. The thing that distinguishes this research from previous research is the object of research and the comparison between research objects. The multiple linear regression analysis method chosen by the author as a research method. This study found that partially, in Surabaya City, only the variable of women's income contribution has a significant negative effect on the poverty rate. Meanwhile, GDI and female labor force participation rate did not have a significant effect. In Gresik district, partially, only GDI has a significant negative effect on the poverty rate. Meanwhile, the women's income contribution and the female labor force participation rate have no significant effect.